A multi-site single blind clinical study to compare the effects of prolonged exposure, eye movement desensitization and reprocessing and waiting list on patients with a current diagnosis of psychosis and co morbid post traumatic stress disorder: study protocol for the randomized controlled trial Treating Trauma in Psychosis - de Bont, Paul AJM (BioMed Central, 2013)
BACKGROUND: Trauma contributes to psychosis and in psychotic disorders post-traumatic stress disorder (PTSD) is often a comorbid disorder. A problem is that PTSD is underdiagnosed and undertreated in people with psychotic disorders. This study’s primary goal is to examine the efficacy and safety of prolonged exposure and eye movement desensitization and reprocessing (EMDR) for PTSD in patients with both psychotic disorders and PTSD, as compared to a waiting list. Secondly, the effects of both treatments are determined on (a) symptoms of psychosis, in particular verbal hallucinations, (b) depression and social performance, and (c) economic costs. Thirdly, goals concern links between trauma exposure and psychotic symptomatology and the prevalence of exposure to traumatic events, and of PTSD. Fourthly predictors, moderators, and mediators for treatment success will be explored. These include cognitions and experiences concerning treatment harm, credibility and burden in both participants and therapists. METHODS/DESIGN: A short PTSD-screener assesses the possible presence of PTSD in adult patients (21- to 65- years old) with psychotic disorders, while the Clinician Administered PTSD Scale interview will be used for the diagnosis of current PTSD. The M.I.N.I. Plus interview will be used for diagnosing lifetime psychotic disorders and mood disorders with psychotic features. The purpose is to include consenting participants (N = 240) in a multi-site single blind randomized clinical trial. Patients will be allocated to one of three treatment conditions (N = 80 each): prolonged exposure or EMDR (both consisting of eight weekly sessions of 90 minutes each) or a six-month waiting list. All participants are subjected to blind assessments at pre-treatment, twomonths post treatment, and six monthspost treatment. In addition, participants in the experimental conditions will have assessments at mid treatment and at 12 months follow-up. DISCUSSION: The results from the post treatment measurement can be considered strong empirical indicators of the safety and effectiveness of prolonged exposure and EMDR. The six-month and twelve-month follow-up data have the potential of reliably providing documentation of the long-term effects of both treatments on the various outcome variables. Data from pre-treatment and midtreatment can be used to reveal possible pathways of change. TRIAL REGISTRATION: Trial registration: ISRCTN79584912